Polyphenol-rich tart cherries (Prunus Cerasus, cv Montmorency) improve sustained attention, feelings of alertness and mental fatigue and influence the plasma metabolome in middle-aged adults: a randomised, placebo-controlled trial. Issue 12 (28th December 2022) - Kimble, Rachel; Keane, Karen M.; Lodge, John K.; Cheung, William; Haskell-Ramsay, Crystal F.; Howatson, Glyn
Abstract: Tart Montmorency cherries (MC) are a particularly rich source of anthocyanins and other polyphenols that have been shown to elicit antioxidant, anti-inflammatory and vasomodulatory actions. The current study aimed to determine the influence of chronic MC supplementation on cognitive function and mood. In a 3-month double-blinded, placebo-controlled parallel study, middle-aged adults (mean ± sd : 48 ± 6 years) were randomly assigned to either 30 ml twice daily of MC ( n 25) or the same amount of an isoenergetic placebo ( n 25). Cognitive function and mood were assessed before and after supplementation using a computerised cognitive task battery and visual analogue scales. Cerebral blood flow was also monitored by near-infrared spectroscopy during the task battery, and questionnaires were administered to determine subjective sleep and health status and plasma metabolomics were analysed before and after supplementation. After 3 months, the MC resulted in higher accuracy in digit vigilance (mean difference: 3·3, 95 % CI: 0·2, 6·4 %) with lower number of false alarms (mean difference: −1·2, 95 % CI: −2·0, −0·4) compared with the placebo. There was also a treatment effect for higher alertness (mean difference: 5·9, 95 % CI: 1·3, 10·5 %) and lower mental fatigue ratings (mean difference −9·5, 95 % CI: −16·5, −2·5 %) with MC. Plasma metabolomics revealed an increase in a number of amino acids in response to MC intake, but not placebo. These data suggest an anti-fatiguing effect of MC supplementation as well as the ability to improve sustained attention during times of high cognitive demand, this could be related to changes in amino acid metabolism.